Optimalisasi Etos Kerja Petani Sedulur Sikep sebagai Upaya Penanggulangan Krisis Pangan - Adhi Surya Perdana (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2013)
Research on work ethos, Sedulur Sikep Communities, done because is seen there is a tendency in the community that working as a farmer can pose a perception that someone has dignity value, spirit, resilience, and work skill away from lie and hold honesty highly through a sense of sincerity on farming, and a support to preserve farming sustainability, so that can be a dignity job to fulfill family and community food needs. The research result shows that work ethos is a drive and an effort to control and evaluate work through a hope and will on farming-activities selves sustain, so that the product gained can be done with responsibility as a real conduct application with an orientation and a goal, give positive value on farmers to prevent family and community food need crisis, and achieve family welfare.